PENGARUH PROSES PEMBELAJARAN DI PERGURUAN TINGGI TERHADAP PERILAKU KEUANGAN DENGAN LITERASI KEUANGAN SEBAGAI VARIABEL INTERVENING - Eni Saraswati, Rispantyo & Djoko Kristianto (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2017)
The purpose of this study to analyze the effect of the learning process in theCollege of the financial literacy and financial behavior and analyze the differencesfinancial literacy by gender and study programs. This study is a survey of students ofthe Economic Faculty Slamet Riyadi University Surakarta. The study population asmany as 351 students. A sample of 70 students by used purposive sampling andproportional cluster random sampling.. Collecting data used questionnaires andliterature study data were analyzed used path analysis and independent sample ttest.The results showed that the learning process in the College of significant effecton the financial literacy of students. The learning process in the College ofsignificant effect on the financial behavior. Financial literacy has a significant effecton the financial behavior. The learning process in the College has effect on thefinancial behavior with financial literacy as an intervening variable No financialliteracy differences between male students and female and there are differences offinancial literacy among students of management courses with accounting courses.Keywords: learning process in the college, financial literacy, financial behavior